ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENERIMAAN AUDITOR ATAS PENYIMPANGAN PERILAKU DALAM AUDIT (Studi Empiris pada Kantor Akuntan Publik di Semarang) - Intan Pujaningrum; Arifin Sabeni (Diponegoro Journal of Accounting, 2012)
Dysfunctional audit behavior represent a reaction of to environment (like operation system). The behavioral can have direct impact to quality of audit. Purpose of which wish to be reached in this research is to test empirically and analyze variable locus of control, organizational commitment, performance, and turnover intention which directly influence acceptance of auditor to dysfunctional behavior. Population in this research is auditors who works at public accountant firm in Semarang in the year 2012. While Determination of sample conducted with (convenience sampling). Sample of 130 responder at 13 KAP can be obtained. Instrument of questionnaire is used to collect data. Analysis of regression is used in this research to prove the hypotheses. Result of research indicate that the variables: locus of control, performance and turnover intention have significant effect to acceptance of dysfunctional audit behavior, while organizational commitment do not have significant effect to acceptance of dysfunctional audit behavior.